Acoustic characteristics of the advertisement call of Trachycephalus atlasBokermann, 1966 (Anura: Hylidae) - Santos-Silva, Carlos Roberto Dos; Ferrari, Stephen F.; Juncá, Flora Acuña (Zootaxa, 2012)
Only three of the 12 recognized species of Trachycephalus Tschudi (Frost 2011) present an occipital crest— Trachycephalus atlas Bokermann, T. nigromaculatus Tschudi, and T. jordani (Stejneger and Test). The latter species is found in Colombia, Ecuador, and Peru. Trachycephalus nigromaculatus is found in the Brazilian Atlantic Forest of São Paulo, Rio de Janeiro, Espirito Santo, Minas Gerais, and southern Bahia states, while T. atlas is restricted primarily to the Caatinga of the Brazilian Northeast (Frost 2011), but overlaps with T. nigromaculatus in the Atlantic Forest of southern Bahia. The two species can be differentiated by the more pronounced posterior cephalic plate, wider inter-orbital distance, and lower and wider head in T. atlas (Bokermann 1966). Herein we describe the acoustic characteristics of advertisement call of T. atlas and compared with other Trachycephalus species.